Long-term outcomes of pseudomyxoma peritonei after cytoreductive surgery and hyperthermic intraperitoneal chemotherapy and its relevant risk factors in China: a retrospective study - Gao, Shuncai; Zhang, Xiang; Yu, Ziyang; Zhang, Junwei (Frontiers in Surgery, 2026)
ObjectivesPseudomyxoma peritonei (PMP), generally spread of low grade appendiceal mucinous neoplasm (mucinous appendix neoplasms) into the abdominal cavity, is conventionally treated with cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (CRS-HIPEC). Prognostic factors of small cohort sizes remain incomplete and conflicting. This large-scale study aimed to characterize long-term survival outcomes and identify prognostic factors in PMP patients following CRS-HIPEC.Materials and methodsWe conducted a retrospective cohort study of 432 consecutive PMP patients treated with CRS-HIPEC at Aerospace Center Hospital (Beijing, China) from June 2014 to December 2020. Overall survival (OS) served as the primary endpoint, with event-free survival (EFS) as the secondary endpoint. Multivariable Cox proportional hazards models were employed to identify independent prognostic factors.ResultsWith median survival durations of 56 months (OS) and 45 months (EFS), cumulative mortality and event incidence reached 21.4% and 32.4%, respectively. Independent predictors for poorer OS included: preoperative raised tumor markers (hazard ratio [HR] = 4.90–10.20; 95% confidence interval [95% CI]: 1.11–46.67; P < 0.05), completeness of cytoreduction (CC) score (HR = 3.37–9.41; 95% CI: 1.05–16.37; P < 0.05), and high-grade PMP (HR = 1.80; 95% CI: 1.10, 2.93; P = 0.019). EFS was significantly associated with preoperative Barthel index (HR = 0.86; 95% CI: 0.74, 0.98; P = 0.019) in addition to the aforementioned factors. Intraoperative hypotension and hyperthermia were not associated with both OS and EFS.ConclusionsKey factors impacting outcomes of patients with PMP of mucinous appendix neoplasms included preoperative elevated tumor markers, Barthel index, CC-score, and the PMP histology, without intraoperative hypotension and hyperthermia.